Bentuk Keislaman dan Keberagamaan Warga Bulu Kabupaten Wonogiri - Setiawan, Rizka; Mujahid, Kasori (ALSYS, 2024)
This research aims to determine Islamic diversity in Indonesia. The research method used is a quantitative method. The results of this research state that 77.8% of society reflects Islamic diversity well. Religion plays a role in regulating human life and directing it towards the common good. Implementing Islam requires sacrifice and struggle. Religion can calm people and religious enthusiasm in Indonesia is good. Spiritual shower activities or Islamic studies make people more enthusiastic about living their lives. And people increasingly understand the contents of the Qur'an and Hadith. The community has the enthusiasm to behave according to the Qur'an and Hadith.